Marketing Strategy in Surabaya City Archives and Library - Fahriyah, Fahriyah (Record and Library Journal, 2015)
Successfull organizations are able to design and manage their information and the supporting technologies as a strategic weapon as well as an information utility. This requires information to be readily available on an as-needed basis to staff, management, customers, suppliers and other stakeholders. The Bodies of Archives and Libraries Surabaya City use the strategic marketing to disseminate information resources at their disposal. The purpose of this research is to know, how the marketing of library in The Bodies of Archives and Libraries Surabaya City. The research method uses literature study with data collection techniques derived from interviews and literature study. For data analysis, the results were processed and analyzed interviews with marketing theory using some of the literature from of books, journals and the results of previous studies. The Bodies of Library and Archive Surabaya city was found some elements in the Marketing Mix or library marketing strategy that has been applied in the library. Adjustment of marketing strategy or concept 7P Marketing Mix are Product, Price, Promotion, Place, People, Process and Physical Evidence in the library have increased performance results The Bodies of Archives and Libraries Surabaya City since 2003 until now.